Environmental pollution and its impact: A study on waste management - Ramadhan, M Faisal; Masjud, Yunita Ismail (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Waste management concentrates on being able to overcome the waste problem, because the problem of waste is no stranger to hearing, so to be better we must be able to control bad behavior, namely littering. Then this is where we live and also where other living beings live, so we must take care of each other in good condition because the environment will affect all aspects. And a good environment can be seen from the cleanliness of the environment itself, such as clean air, cool and clear water, then managing waste properly and being able to plant more trees so that the environment can re-green the area. However, garbage still destroys the surrounding environment. For the development of a healthy environment, we must be self-aware to protect our homes by minimizing the use of plastic and for waste-producing companies to be able to manage it properly, not to damage the environment by disposing of its waste carelessly. Because to deal with waste management, this company aims to utilize B3 waste. and non-B3. and better to protect the environment using materials that can be recycled.